2019
DOI: 10.7554/elife.50830
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid and tau accumulate across distinct spatial networks and are differentially associated with brain connectivity

Abstract: The abnormal accumulation of amyloid-β and tau targets specific spatial networks in Alzheimer’s disease. However, the relationship between these networks across different disease stages and their association with brain connectivity has not been explored. In this study, we applied a joint independent component analysis to 18F- Flutemetamol (amyloid-β) and 18F-Flortaucipir (tau) PET images to identify amyloid-β and tau networks across different stages of Alzheimer’s disease. We then assessed whether these patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 75 publications
(119 reference statements)
5
67
1
Order By: Relevance
“…Thus, CSF NfL is a risk factor for cognitive impairment for those on the AD pathway (with low CSF Aβ42 levels) and for those who are not. Our results are also consistent with studies that have shown that elevated CSF NfL levels reflect neurodegeneration in AD 6,9,24 and in many other neurological diseases. 24 Thus, CSF NfL is a nonspecific marker of neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, CSF NfL is a risk factor for cognitive impairment for those on the AD pathway (with low CSF Aβ42 levels) and for those who are not. Our results are also consistent with studies that have shown that elevated CSF NfL levels reflect neurodegeneration in AD 6,9,24 and in many other neurological diseases. 24 Thus, CSF NfL is a nonspecific marker of neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Our results extend this finding earlier in the clinical disease spectrum by showing that high CSF NfL levels are also strongly associated with risk of MCI in a community-based study of CU partici-pants. Our findings are also consistent with ADNI results suggesting that CSF NfL was associated with cortical and subcortical brain atrophy, 6,9 which should translate into cognitive progression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The classical degeneration pattern accompanying disease progression is characterized by lower anisotropy and higher diffusivity, representing loss of coherence in the white matter microstructure with AD progression (Caso et al, 2016;Sexton et al, 2011). This pattern of white matter degeneration develops invariably along the AD spectrum (Amlien and Fjell, 2014;Pereira et al, 2019), with associations often becoming detectable only in the mild cognitive impairment and dementia stages (Mito et al, 2018;Song et al, 2018;Wang et al, 2019;Wen et al, 2019), and very few in Aβ-positive cognitively normal participants (Rieckmann et al, 2016;Vipin et al, 2019). However, our consistent pattern of more restricted diffusion (higher FA and lower MD) being associated with more pathology in three bundles suggests that microstructural alterations captured with diffusion MRI might differ in the preclinical vs. the symptomatic phase of AD, during which severe and irreversible atrophy has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, multimodal neuroimaging techniques have been used to unravel the impact of Tau and Aβ accumulation on both GM and WM pathology. Functional MRI (fMRI) studies show reduced activity of functional networks and connectivity (Sepulcre et al, 2017, Pereira et al, 2019, Son et al, 2017, while diffusion-weighted MRI (DWI) studies demonstrate impaired WM integrity in AD (Agosta et al, 2011, Acosta-Cabronero et al, 2010. To determine the WM properties, Tract-based spatial statistical (TBSS) analytical technique has been used over the years in various disease contexts.…”
Section: Introductionmentioning
confidence: 99%